Digital expression profile of immune checkpoint genes in medulloblastomas identifies CD24 and CD276 as putative immunotherapy targets - Marques, Rui Ferreira; Moreno, Daniel Antunes; da Silva, Luciane; Leal, Leticia Ferro; de Paula, Flávia Escremim; Santana, Iara; Teixeira, Gustavo; Saggioro, Fabiano; Neder, Luciano; Junior, Carlos Almeida; Mançano, Bruna; Reis, Rui Manuel (Frontiers in Immunology, 2023)
Introduction: Medulloblastoma is the most common and lethal pediatric malignant brain tumor. It comprises four main molecular subgroups: WNT-activated, SHH-activated, Group 3, and Group 4. Medulloblastoma treatment is surgical resection, craniospinal radiation, and chemotherapy. However, many patients do not respond to therapy, and most suffer severe side effects. Cancer immunotherapy targeting immune checkpoints (IC) (PD-1, PD-L1, and CTLA4) has been getting disappointing outcomes in brain tumors. Nevertheless, other less explored immune checkpoints may be promising candidates for medulloblastoma therapy. Objectives: In the present study, we aimed to characterize the expression profile of 19 immune checkpoints in medulloblastoma. Methods: We analyzed 88 formalin-fixed paraffin-embedded medulloblastomas previously classified for each molecular subgroup and three non-tumoral brain tissue. mRNA levels of 19 immune checkpoint-related genes were quantified using the nCounter (PanCancer Immune Profiling Panel) assay. Further in silico analysis was performed in two larger public microarray datasets, one of which enabled comparisons between tumoral and non-tumoral tissues. Immunohistochemistry of PD-L1 was performed in a subset of cases. Microsatellite instability was also molecularly analyzed. Results: We observed an absence of expression of the canonic ICs, namely PDCD1 (PD-1), CD274 (PD-L1), and CTLA4, as well as CD80, CD86, BTLA, IDO1, CD48, TNFSF14, CD160, CEACAM1, and CD244. PD-L1 protein expression was also practically absent. We found higher mRNA levels of CD24, CD47, CD276 (B7-H3), and PVR, and lower mRNA levels of HAVCR2, LAG3, and TIGIT genes, with significant differences across the four molecular subgroups. Compared to the non-tumor tissues, the expression levels of CD276 in all subgroups and CD24 in SHH, Group 3, and Group 4 subgroups are significantly higher. The in silico analysis confirmed the expression profile found in the Brazilian cohort, including the lower/absent expression of the canonic ICs. Moreover, it confirmed the overexpression of CD24 and CD276 in medulloblastomas compared with the non-tumor tissue. Additionally, CD276 and CD24 high levels were associated with worse survival. Conclusion: These results highlight the low or absence of mRNA levels of the canonic targetable ICs in medulloblastomas. Importantly, the analysis revealed overexpression of CD24 and CD276, which can constitute prognostic biomarkers and attractive immunotherapy targets for medulloblastomas.